Radiation therapy for prostate cancer in Syrian refugees: facing the need for change - Eren, Mehmet Fuat; Kilic, Sarah S.; Eren, Ayfer Ay; Kaplan, Sedenay Oskeroglu; Teke, Fatma; Kutuk, Tugce; Bicakci, Beyhan Ceylaner; Hathout, Lara; Moningi, Shalini; Orio, Peter; Atalar, Banu; Sayan, Mutlay (Frontiers in Public Health, 2023)
Purpose: To report the utilization of radiation therapy in Syrian refugee patients with prostate cancer residing in Turkey. Methods and Materials: A multi-institutional retrospective review including 14 cancer centers in Turkey was conducted to include 137 Syrian refugee patients with prostate cancer treated with radiation therapy (RT). Toxicity data was scored using the National Cancer Institute Common Terminology Criteria for Adverse Events version 3.0. Noncompliance was defined as a patient missing two or more scheduled RT appointments. Results: Advanced disease, defined as stage III or IV, was reported in 64.2% of patients while androgen deprivation therapy (ADT) was only administrated to 20% of patients. Conventionally fractionated RT with a median number of 44 fractions was delivered to all patients with curative intent (n=61) while palliative RT (n=76) was delivered with a median number of 10 fractions. The acute grade 3-4 toxicity rate for the entire cohort was 16%. Noncompliance rate was 42%. Conclusions: Most Syrian refugee prostate cancer patients presented with advanced disease however ADT was seldom used. Despite the low treatment compliance rate, conventional fractionation was used in all patients. Interventions are critically needed to improve screening and increase the use of standard-of-care treatment paradigms, including hypofractionated RT and ADT.